2001
DOI: 10.1002/ana.1159
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the extended tau haplotype to tau biochemistry and neuropathology in progressive supranuclear palsy

Abstract: Two extended haplotypes of the tau gene (H1 and H2) have been described. The frequency of H1 haplotype is increased in progressive supranuclear palsy (PSP). PSP is associated with filamentous tau lesions in neurons and glia, which are reportedly composed exclusively of tau isoforms with four repeats in the microtubule-binding domain (4R tau). To determine the influence of the tau haplotype on tau isoform composition and neuropathology, we studied 25 PSP cases and 6 Alzheimer's disease patients matched for age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 38 publications
5
27
1
Order By: Relevance
“…Previous studies have identified a strong association between the dinucleotide repeat polymorphism A0 and the risk of PSP, CBD and FTD [11 -13]. Remarkably, reports in PSP have shown no relation of the A0/A0 genotype to the biochemical characteristics such as tau deposit composition or to the clinical phenotype [14]. Also in ALS, we found no association of the A0/A0 genotype with the age and site of disease onset or the presence of dementia.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies have identified a strong association between the dinucleotide repeat polymorphism A0 and the risk of PSP, CBD and FTD [11 -13]. Remarkably, reports in PSP have shown no relation of the A0/A0 genotype to the biochemical characteristics such as tau deposit composition or to the clinical phenotype [14]. Also in ALS, we found no association of the A0/A0 genotype with the age and site of disease onset or the presence of dementia.…”
Section: Discussioncontrasting
confidence: 74%
“…Specifically, this group of diseases may include PSP, CBD, argyrophilic grain disease, and other FTDP-17 diseases resulting from exon 10 splicing mutations (Mailliot et al, 1998;Sergeant et al, 1999;Arai et al, 2001;Liu et al, 2001;Katsuse et al, 2003;Morris et al, 2003). These tauopathies all have similar characteristics of astrocytic and neuronal tau accumulation, predominantly 4R insoluble tau and motor and cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…All blots were incubated with a blocking solution containing 5% nonfat milk, 0.1% goat serum and 0.1% Tween-20 in TBS, incubated with various antibodies, and washed as previously described. 5,9,33 The washed blots were incubated for 1 hour at room temperature with peroxidase-conjugated, goat anti-rabbit (1:4000, Chemicon, Temecula, CA), anti-mouse IgG (1:2000, Bio Rad, Hercules, CA), followed with washing and detection of bound antibodies with the enhanced chemiluminescence system (ECL plus; Amersham Biosciences, Piscataway, NJ). Immunoreactivity of GSK3 proteins was analyzed from scanned films using MCID software (Imaging Research Inc., Ontario, Canada).…”
Section: Western Blottingmentioning
confidence: 99%